Optimalisasi Beauty Preunership Melalui Pelatihan Nail Art pada Homestaff dan Localstaff KBRI Manila - Nia Kusstianti; Dewi Lutfiati; Arita Pupitorini; Mutimmatul Faidah; Sri Dwiyanti; Sri Usodoningtyas; Dindy Sinta Megasari; M.A. Hanny Ferry Fernanda (Politeknik Piksi Ganesha Indonesia, 2025)
The Embassy of the Republic of Indonesia (KBRI) in Manila has residents who live around the KBRI or are commonly called Local Staff and Home Staff. They consist of workers in the KBRI itself or independent workers. The Local Staff and Home Staff are male and female workers, however, more of them are women. They need other skills to support their main skills as workers. Unesa through the Community Service Team of the Makeup Education Study Program answers this need by providing training in nail art skills with the aim of providing capital for entrepreneurship in the beauty sector (beauty preneurship). The training is carried out using lecture, demonstration and guided practice methods. Through the training, the response obtained was positive and cooperation was established between the Local Staff and Home Staff of the Indonesian Embassy in Manila with the Makeup Education Study Program. and can improve the entrepreneurial spirit and creativity through the skills provided.